2016
DOI: 10.1109/led.2016.2519680
|View full text |Cite
|
Sign up to set email alerts
|

Compatibility of AlN/SiNxPassivation With LPCVD-SiNxGate Dielectric in GaN-Based MIS-HEMT

Abstract: In this letter, we demonstrate an integrated process that illustrates the compatibility of AlN/SiN x passivation with high-performance (i.e. low leakage and high breakdown) low-pressure chemical vapor deposition (LPCVD) SiN x gate dielectric for GaN-based MIS-HEMT. It is shown that the AlN/SiN x passivation structure maintains its superior capability of suppressing the current collapse after enduring high temperature of 780°C during the LPCVD-SiN x deposition. The AlN/SiN x passivation is shown to be significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 13 publications
1
21
0
1
Order By: Relevance
“…高温LPCVD技术不仅可以用来制备高质量的钝 化介质, 也是制备高绝缘氮化物栅介质(如SiNx)的良好 方法 [33,[44][45][46][47] . 如图22所示, LPCVD-SiNx与GaN间的导带 带阶为2.75 eV, 而且自身的击穿场强达到13 MV/cm [47] , 显著高于PECVD-SiNx栅介质, 因此LPCVD-SiNx栅介 质适合制备高压GaN基MIS-HEMT器件, 可进一步扩 展栅极的安全阈值范围.…”
Section: Lpcvd-sinx栅介质技术及可靠性unclassified
“…高温LPCVD技术不仅可以用来制备高质量的钝 化介质, 也是制备高绝缘氮化物栅介质(如SiNx)的良好 方法 [33,[44][45][46][47] . 如图22所示, LPCVD-SiNx与GaN间的导带 带阶为2.75 eV, 而且自身的击穿场强达到13 MV/cm [47] , 显著高于PECVD-SiNx栅介质, 因此LPCVD-SiNx栅介 质适合制备高压GaN基MIS-HEMT器件, 可进一步扩 展栅极的安全阈值范围.…”
Section: Lpcvd-sinx栅介质技术及可靠性unclassified
“…The "virtual gate" caused by surface/interface trapping is suppressed, and the GaN HEMTs with SiN x passivation layer can deliver mitigated current collapse [6]. However, the SiN x passivated devices typically exhibit a significant increase in dynamic R ON after high voltage stress (off-state drain bias > 100 V) [12][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is well known that the problem of current collapse is due to electron trapping in the interface between AlGaN and surfaces [11]- [13]. The interface problem has been discussed before, and many groups have tried to solve it using various passivation materials (SiN X , AlN, and polyimide), surface treatments (post-gate annealing and various types of plasma), and edge termination (gate-and source-field plates) [14]- [18]. In addition, it was recently reported that GaN buffer traps play a role in off-state leakage and dynamic on-resistance.…”
Section: Introductionmentioning
confidence: 99%